Malice in Crimes in Iran and The English Criminal Law - Peyman Rostamian; Mohammad Hossein Hajjarian; Hassan Ali Moazzanzadegan (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2019)
AbstractThe presence of a psychological relationship between the act and the agent, and the importance of the intent and the classification of crimes into intentional and unintentional crimes, the punishment of the perpetrators of these crimes differed so that today in the distinction between civil and criminal liability, the condition of the psychological element in the proofs of the titles of criminal acts is necessary, so long as it is said that the principle is the deliberate nature of the offenses and the contrary is required to be specified. Therefore, the current paper aims at investigating the malic in crimes in Iran and The United Kingdom. the conceptual research subject is expanded and then, qualitative research method was used to analyze the data collected from library sources using the legal literature analysis method. The findings indicate that: